Active Layer Dynamics at Four Borehole Sites in Western Dronning Maud Land, Antarctica - Kotzé, Camilla (Rhodes University, Faculty of Science, Department of Geography, 2016)
Permafrost and active layer dynamics in the Antarctic play an important role within terrestrial landscapes and ecosystems and as a climate change indicator. However, they remain less thoroughly researched than their Northern-Hemispheric counterpart. Despite advancements made by ANTPAS on the permafrost and active layer monitoring network in the Antarctic, observational gaps still exist. Western Dronning Maud Land (WDML) has been identified as one of these gaps, necessitating further research on permafrost dynamics and the influence of climate parameters thereon. Such elucidation is critical to both the cryospheric and life sciences. Variations in the surface climate of Antarctica can be seen as a result of inter-annual variations in atmospheric circulation, enhancing permafrost degradation and active layer thickening which directly affects soil processes, such as sorting and cryoturbation. Ground temperatures from four permafrost boreholes from WDML were analysed from 2007 to 2014. The study sites exhibit seasonal freezing, periglacial landforms, and altitudinal variation, ranging between ca. 450masl to ca. 1300masl. Using ground thermal regime and regional climate data, the spatial and temporal variability of the active layer in the Ahlmannryggen and Jutulsessen areas of WDML were characterised. 137 Cs tracing has revealed that the active layer and associated landforms have been active over the past half century. Further results show that active layer depths at each site vary inter-annually and are particularly influenced by snow cover, altitude and distance to the ice-shelf. Moreover, a correlation between the SAO (Semi-Annual Oscillation) and measured ground temperatures was found, principally during the transitional season of the SAO in May and September. The relationship between climate and ground thermal regimes, especially the influence of teleconnections thereon, is essential to improving the understanding of permafrost dynamics and landform morphology in continental Antarctica.
Keywords: Uncatalogued